Effect of insulin adherence educational application on adherence and glycemic control in diabetes mellitus patients - Prasaja, Sehat Dwi; Elsanti, Devita (Institute Of Computer Science (IOCS), 2025)
Diabetes mellitus is a chronic disease that requires lifelong management. Patient adherence to insulin use and glycemic control are crucial factors in diabetes mellitus management. However, low adherence and limited knowledge about insulin usage remain common issues. This study aims to evaluate the effect of the Insulin Adherence Educational Application on insulin adherence and glycemic control in patients with type 2 diabetes mellitus. This study employed a pre-experimental design with a pre-test and post-test without a control group. A total of 18 patients with type 2 diabetes mellitus at Prof. Dr. Margono Soekarjo Hospital were selected using purposive sampling. Data collection was conducted through questionnaires and glycemic level examinations. Paired t-test and Wilcoxon test were used for data analysis. The results showed a significant increase in family support, insulin adherence, and glycemic control after the intervention using the educational application (p < 0.05). The Insulin Adherence Educational Application effectively enhances family support, insulin adherence, and glycemic control in patients with type 2 diabetes mellitus. This research provides education, an Android application (aksi patas) to patients suffering from diabetes mellitus, which includes interesting features, especially about diabetes mellitus.